Mobility, phytotoxicity and removal of nanomaterials in a natural water sample / Shanaz Jahan - Shanaz , Jahan (2018)
This research explored the mobility, phytotoxicity and removal of nanomaterials (NMs), in a natural water sample. In this research three metal based NMs, including one newly synthesized polyethylene imine coated silver nanoparticles, PEI@AgNPs (50 ± 10 nm) and two already reported polyethylene glycol coated zinc oxide nano-rods, PEG@ZnONRs (64 ± 10 nm) and uncoated titanium dioxide nanoparticles, TiO2NPs (89 ± 20 nm) were synthesized. To investigate the effect of morphology, two more zinc oxide structures, i.e., zinc oxide nano-needles, ZnONNs (43 ± 10 nm) and zinc oxide micro-flowers, ZnOMFs (1.09 ± 0.2 μm) were also produced. Carbon based NMs comprising of carbon nanoparticles, CNPs (20± 10 nm) and graphene oxide quantum dots, GOQDs (50 ± 20 nm) were synthesized by following earlier work. Packed column experiments were systematically performed to explore the behavior of metal and carbon based NMs using natural river water as flowing medium. For NMs mobilization behavior, two metal based NMs i.e., PEG@ZnONRs and TiO2NPs were selected and analyzed under hydroponic plant growth. The results obtained from the column transport experiments of metal based NMs revealed that, the surface coating play important role in the particle dissolution and ionic metal release. Typically, the ionic metals release i.e., Ag(I), Zn(II) and Ti(IV) were 3 %, 19 % and 12 % from PEI@AgNPs, PEG@ZnONRs and TiO2NPs respectively. The findings obtained from the size and morphology effects depicted that, ZnONNs with small particle size (43 ± 10 nm nm) and simple needle shaped morphology was transported well compared to PEG@ZnONRs (64 ± 10 nm), and ZnOMFs (1.09 ± 0.2 μm) with large particle sizes and angular structures. The transport behavior of carbon based NMs was largely driven by the particle surface charge. CNPs with high surface charge (-40 mV) transported more from the column compared to GOQDs (-24 mV). In addition, the presence of monovalent salt (NaCl) significantly affects the transport behavior of metal and carbon based NMs. Whereas, limited response was observed in the presence of divalent salt (CaCl2). The findings achieved from the metal ion mobilization into the plant revealed that, Zn(II) ions due to the generation of oxidative stress significantly inhibit the physiological and biochemical activity of plant even at small concentration (40 μg/mL). In contrast, no adverse effects of Ti(IV) ions were observed at concentrations up to 200 μg/mL. This contrast finding was due to the distinct mobilization pattern indicating that, both metal ions exert different effects under similar environmental conditions. In remediation part, polymer modified mesoporous silica iron microcubes (P@MSIMC) adsorbent was successfully synthesized. The maximum removal efficiency of adsorbent for PEG@ZnONRs, TiO2NP and PEI@AgNPs was 850 mg/g, 720 mg/g and 550 mg/g while, 600 mg/g and 504 mg/g for CNPs and GOQDs respectively. The kinetics of adsorption process fitted well with the pseudo-second-order kinetic model. Furthermore, the adsorption process was predominantly unaffected in presence of natural water coexisting ions suggesting that, the synthesized adsorbent is excellent for the remediation of metal and carbon based NMs from natural aqueous medium.